2020
DOI: 10.1177/0739532920968219
|View full text |Cite
|
Sign up to set email alerts
|

The price of greater representation: A cross-national analysis of parliamentary representation and media coverage sentiment for women

Abstract: Previous research suggested that news media coverage tone tends to become more negative for successful women in politics (but not for successful men) when compared with less successful and well-known women. This study tests this in 17 countries. Specifically, it examines relationships between greater parliamentary representation of women and the coverage tone in articles on women in that country through a computational analysis of millions of persons’ names in more than 1,000 newspapers. Growth in parliamentar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The latter received more coverage of their appearance and personal life, more negative coverage of their political viability, and more stereotypical trait coverage (Aaldering and Van der Pas 2020, Van der Pas and Aaldering 2020). In another recent cross-national study, Shor and Miltsov (2020) found that growth in the parliamentary representation of women was associated with more negative coverage to women in various countries.…”
Section: Gender Fame and Media Coverage: Existing Evidencementioning
confidence: 95%
“…The latter received more coverage of their appearance and personal life, more negative coverage of their political viability, and more stereotypical trait coverage (Aaldering and Van der Pas 2020, Van der Pas and Aaldering 2020). In another recent cross-national study, Shor and Miltsov (2020) found that growth in the parliamentary representation of women was associated with more negative coverage to women in various countries.…”
Section: Gender Fame and Media Coverage: Existing Evidencementioning
confidence: 95%
“…Computational methods include a gamut of different techniques including machine learning (e.g., deep learning, statistical learning, reinforcement learning), social network analysis, text and data mining (e.g., sentiment analysis, topic modelling, named‐entity recognition), agent‐based modelling, more flexible regression/estimation models (e.g., regression shrinkage and selection, Bayesian statistics, spatial regression models), advances in survey methods (e.g., survey experiments, optimum design, respondent‐driven sampling), and so on. Some sociologists in Canada have contributed directly to the development of particular methods (Alexander & Alkema, 2021; Andersen, 2008; Bignami‐Van Assche et al., forthcoming; Fosse & Winship, 2019; Fox, 2015; Fox & Andersen, 2006; Fu et al., 2020, 2021; Hayduk, 1996; Li et al., forthcoming; Miles, 2016; Nelson, 2020; Stecklov et al., 2018; Wellman et al., 2003, 2020), but more often sociologists have embraced and adapted methods developed by computer scientists, statisticians, and econometricians (Abul‐Fottouh et al., 2020; Boase, 2016; Das, 2022; Gallupe et al., 2019; Gruzd & Mai, 2020; Gu et al., 2021; Hogan & Berry, 2011; Howe et al., forthcoming; Kudla & Parnaby, 2018; Letarte et al., 2021; Li & Luo, 2020; McLevey, 2022; McMahan & McFarland, 2021; Quan‐Haase et al., 2021; Richardson et al., 2021; Roth et al., forthcoming; Shor & Miltsov, 2020; Shor et al., 2013; Silver & Silva, 2021; Smith, 2020; Sytsma et al., 2021; Veenstra & Vanzella‐Yang, 2022; Yuan et al., 2022).…”
mentioning
confidence: 99%